SISTEM PENDUKUNG KEPUTUSAN PENILAIAN KINERJA GURU PADA SMP AR ROUDLOH JEGULO MENGGUNAKAN METODE SAW (Simple Additive Weighting) BERBASIS WEB - Ita Aristia Sa’ida; Ayu Mauliana Intahaya (Jurnal Inovasi Penelitian, 2022)
In line with human resource development as a national development priority, teacher performance appraisal is increasingly strategic in preparing quality human resources for the global era. The problems that occur in the process of evaluating teacher performance appraisal of quality standards for teachers in schools, especially at SMP Ar Roudloh Jegulo, are still subjective. To reduce the nature of the subjectivity, it is necessary to design a teacher performance appraisal system using the SAW method as a basis for decision making. The SAW method is a multi-criteria decision-making method. The number of criteria is what makes it difficult for management to give weight to each criterion. Therefore, a decision support system is needed, which is looking for the best alternative with the SAW calculation process to determine teacher performance recommendations. In teacher performance appraisal with the objectives achieved in this study, namely the creation of adequate teacher performance and can assist schools in making relevant decisions for teacher performance appraisal using the SAW method with the hope of improving the performance and achievement of other teachers. The data collection method used is literature study and interview. The system development method used in this system is the SAW method. With this system it is intended to simplify and accelerate in determining employee performance appraisal at SMP Ar Roudlo Jegulo and it is expected that according to user needs.